A psychoanalytic qualitative study of subjective life experiences of women with breast cancer - (:unkn) unknown (Athabasca University, 2012)
This article exemplifies research on the subjective life experiences of women with breast cancer, designed from a psychoanalytic perspective. Such research aims to reveal the subjective intrapsychic processes of women suffering from breast cancer, which can provide researchers and health care professionals with useful insight. Using Biographic narrative interpretative method, the study reveals some common denominators in the subjective life experiences of women with breast cancer. The study revealed that the subjects consider the diagnosis of breast cancer as one of the four main events in their lives. Even though these events are very different from each other, in terms of type and severity, the results indicate a common process in the way these life events are experienced by the participants. These results are relevant for health care practitioners in structuring their psychosocial support programs so as to better accommodate their patients' psychological needs. © 2012 Journal of Research Practice and the author.
Keywords: Breast cancer; Coping strategy; Life event; Narrative interview; Narrative research; Psychodynamic research; Research frameworks and Paradigms; Research method; Subjective experience